Why pollution standards are preferred by industries: pragmatism and rent-seeking behaviour - Abdul Rahim, Khalid (Chapman & Hall, 1996)
Regulatory instruments in environmental policy have strongraison d'etre. They still dominate the instruments selected by policy makers. Even with the growing interest in the use of economic instruments, in theory, empirical studies and policy, industries tend to prefer command-and-control as a practical instrument in pollution control. Polluters often assume they have more influence on regulation than on setting effluent charge levels. The industry can be better off under the regulatory standard than an imposed effluent charge when the total cost of abatement to the industry is considered. The higher costs to the industry make effluent charges less attractive. In practice, generally a ‘mixed’ environmental policy is used in which regulations dominate. This choice has been based on effectiveness, economic efficiency and political acceptability. By simulating the abatement cost function, it was found that marketable permits offer an attractive system of pollution control when the scope of variation in abatement levels is evident. Unfortunately, at higher levels of abatement, the benefits of this system are small and insufficient to justify any regulatory reform. Thus, with a pragmatic approach coupled with a rent-seeking behaviour of the polluters, a shift to the use of economic instruments is neither likely nor desirable even when administrative and transactions costs are not considered.